2020
DOI: 10.1016/j.jmb.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein L11 Selectively Stabilizes a Tertiary Structure of the GTPase Center rRNA Domain

Abstract: The GTPase Center (GAC) RNA domain in bacterial 23S rRNA is directly bound by ribosomal protein L11, and this complex is essential to ribosome function. Previous cocrystal structures of the 58-nucleotide GAC RNA bound to L11 revealed the intricate tertiary fold of the RNA domain, with one monovalent and several divalent ions located in specific sites within the structure. Here, we report a new crystal structure of the free GAC that is essentially identical to the L11-bound structure, which retains many common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Although we cannot further characterize these compact conformations, we do have some insight into their role in the biology of the GAC. We note that recent measurements ( 39 ) showed that, in the absence of Mg 2 + , GAC RNA has negligible affinity for the L11 protein. In prokaryotes, L11 protein binding to the GAC rRNA in the large ribosomal subunit is necessary for efficient translation.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although we cannot further characterize these compact conformations, we do have some insight into their role in the biology of the GAC. We note that recent measurements ( 39 ) showed that, in the absence of Mg 2 + , GAC RNA has negligible affinity for the L11 protein. In prokaryotes, L11 protein binding to the GAC rRNA in the large ribosomal subunit is necessary for efficient translation.…”
Section: Discussionmentioning
confidence: 51%
“…All systems were prepared from the available crystal structure of GAC in its folded state (PDB ID: 1HC8 [38], see Figure 2) after removing the bound protein. We notice that a recent RNA-only crystal structure is virtually identical [39]. The system was described using the AMBER force field for nucleic acids [40,41,42], the 4-point optimal-point-charge (OPC) model for water [43], and compatible ion parameters [44,45].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Finally, our findings here highlight how protein binding can contribute to RNA structural changes. In a recent study, we showed that proteins partners can help stabilize RNA structure (55). Work by other groups also showed the generality of mechanisms in which proteins help fold RNA.…”
Section: Discussionmentioning
confidence: 89%
“…In particular, the experiments suggested that K + favored more extended conformations of GAC, while Mg 2+ favored the folded state. Notably, our systems were constructed with the RNA molecule in its folded conformation, as found in crystal structures [21,45]. Nevertheless, it is interesting to note that none of the solvent conditions that we examined found agreement with neither of the experimental SAXS spectra.…”
Section: Discussionmentioning
confidence: 96%